One-step synthesis of Lycopodium alkaloid (-)-huperzine W via Suzuki-Miyaura coupling - Xu, Tao (Springer Berlin Heidelberg, 2012)
The first total synthesis of (−)-huperzine W (1) has been achieved. Key element of the synthesis is a highly convergent assemblage for the two rings system of target molecule utilizing an efficient Suzuki-Miyaura coupling reaction between chiral iodide 2 and 2-allylpyrrolidinone 4. Evaluation of the AchE inhibition of synthetic huperzine W was also carried out. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-012-0084-2 and is accessible for authorized users.